Disseminated non typhoidal salmonella infection with salmonella pneumonia and vertebral osteomyelitis in sickle cell disease: A case report. (2022) - Elnour, Salma; Hashim, Maram; Ibrahim, Halah
Abstract: Non-typhoidal salmonella (NTS) is most commonly associated with self-limiting enterocolitis. However, in extremes of age and immune compromised patients, it can cause invasive and disseminated infection, including bacteremia and localized extraintestinal infections. Pneumonia and vertebral osteomyelitis are rare manifestation of NTS, with only a few cases reported worldwide. Our case describes a young man with sickle cell anemia, who developed multifocal invasive NTS infection with pulmonary involvement, vertebral osteomyelitis, and epidural abscess. He was treated with a six-week course of antibiotics and surgical drainage of the abscess. This case report highlights an atypical presentation of NTS infection that is associated with high morbidity and mortality, that can be reduced with early diagnosis and appropriate treatment.